Prediction of Scoliosis Curve Correction Using Apical Fulcrum Bending Radiographs in Adolescent Idiopathic Scoliosis (AIS) - Javeria Junaid; Saddam Mazar; Shahzaib Riaz Baloch; Fatima Bashir; Mohammed Sohail Rafi; Imtiaz Ahmed Hashmi (ziauddin University, 2024)
Background: Scoliosis is defined as a three-dimensional deformity of spine. Surgical treatment is indicated for curves equal to/or more than 40 degrees in magnitude. Curve flexibility is determined preoperatively through bending films, which help in the selection of fusion levels. Surgical treatment for fully-grown spine is a spinal fusion use to inhibit the progress of deformity which further helps in balancing of both sagittal and coronal planes. Therefore, this study aimed to find out the association between predicted via bending films after correction and final surgical correction of skeletally mature patients with Adolescent Idiopathic Scoliosis (AIS). Methods: Thirty-three patients with Adolescent Idiopathic Scoliosis (AIS) were recruited for the study. Those patients were operated at Dr. Ziauddin University Hospital, Karachi from June 2016 to June 2020. Using Pre- and post-operative radiographs of the spine, Cobb values were used to calculate the percentage of correction achieved. Percentage correction (surgical) was then compared to correction possible (predicted) to find association via an independent t-test with p<0.05 considered as statistically significant. Results: Out of total 33 patients, 24 (72.7%) were females and 9 (27.2%) were males. The mean age of the patients was 17.2±3.0 years. Using bending films, correction of the scoliotic deformity was predicted through measured angles with 78±18°. The corrections' difference was 84.5±11°. This difference was found to be statistically insignificant (p=0.0769) which showed no difference in predicted and actual correction achieved. Conclusion: In skeletally mature patients with AIS, bending films have been shown to accurately predict the amount of postoperative correction of Cobb's angle which is possible. Keywords: Age Determination by Skeleton; Scoliosis; X-Ray Film; Spinal Curvatures.